The Scientist as Statesman: Biologists and Third World Health - Carvalho, John J. (Zygon, 2007)
Abstract. One of the most threatening problems the world faces is the growing poverty crisis and the related human rights inequalities and the spread of diseases in underprivileged areas. Human rights and relief organizations try hard to contain the devastation of these interconnected difficulties. What is the role of the biomedical scientist in this endeavor? The challenges that biomedical scientists face in their research lead us to question whether scientists can go beyond the time-consuming realm of experimental investigation and engage the issues of society in a more public way. I suggest how the scientist's role can be expanded in our complex and precarious world, introducing the idea of the modern biomedical researcher as scientist, scholar-philosopher, and statesman for the scientific community and the larger human rights community. I provide examples of where the scientist can interface with human rights organizations, medical doctors, political and civic leaders, and the science-religion dialogue. My argument reveals the emerging role of the biomedical scientist as one of public service in addition to and beyond the realm of the experimental investigator. This role, however, is formidable, and I list some of the obstacles it entails.